Practical aspects of establishing (changing) the boundaries of administrative and territorial unit - Dorosh, O.; Ibatullin, S.; Tarnopolskyi, Ye.; Kharytonenko, R. (Land Management, Cadastre and Land Monitoring, 2019)
In order to establish (change) the boundaries of administrative-territorial entities using the example of Malaya Olshanka village, Belotserkovsky district, Kiev region, pre-project studies were conducted, namely: the materials of the master plan, the project of forming the boundaries of the village council and establishing its boundaries, the existing cartographic and topographical data were analyzed land cadastre, land-registration data. In addition, a reconnaissance survey was conducted on the territory of the village council in the zone of the existing and project boundary (defined by the master plan) of the specified rural settlement. It was established that a significant part of the project boundary according to the general plan divides land plots of landowners and land users, contours of land, contributes to the formation of enclaves in accordance with the law, in case of approval of such a limit will require the separation of such sites.The need for a combination of urban planning documentation (master plan) with land management (land management project to establish (change) the boundaries of administrative-territorial entities) into a unified system of spatial (territorial) planning to create an effective tool in solving problems related to the formation and establishment of boundaries.Key words: project of land management, establishment of boundaries, change of boundaries, boundary of the settlement, administrative and territorial entity, master plan, spatial planning.